2004
DOI: 10.1083/jcb.200403093
|View full text |Cite
|
Sign up to set email alerts
|

The death receptor antagonist FAIM promotes neurite outgrowth by a mechanism that depends on ERK and NF-κB signaling

Abstract: Fas apoptosis inhibitory molecule (FAIM) is a protein identified as an antagonist of Fas-induced cell death. We show that FAIM overexpression fails to rescue neurons from trophic factor deprivation, but exerts a marked neurite growth–promoting action in different neuronal systems. Whereas FAIM overexpression greatly enhanced neurite outgrowth from PC12 cells and sympathetic neurons grown with nerve growth factor (NGF), reduction of endogenous FAIM levels by RNAi decreased neurite outgrowth in these cells. FAIM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(92 citation statements)
references
References 40 publications
3
88
0
1
Order By: Relevance
“…As FAIM was highly expressed in spleen and thymus, 7,8 we characterized B-and T-cell development in faim À/À mice. Flow cytometry analyses revealed that mutant mice had normal B and T lymphopoiesis ( Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As FAIM was highly expressed in spleen and thymus, 7,8 we characterized B-and T-cell development in faim À/À mice. Flow cytometry analyses revealed that mutant mice had normal B and T lymphopoiesis ( Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…FAIM is expressed in neurons and has been shown to regulate neurite outgrowth 8 and neuronal survival. 9 It is possible that FAIM could play a more critical role in the nervous system and we are currently assessing its involvement in Parkinson's and Alzheimer's diseases where massive neuronal cell death is known to occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PC12 cells stably transfected with IκBα super-repressor (SR-IκBα)-pcDNA3 or empty-pcDNA3 vectors were obtained as described by Sole et al [45]. For RNAi experiments, constructs were generated in pSUPER.retro.puro (OligoEngine, Seattle, WA) using specific oligonucleotides targeting Bcl-x L , c-FLIP or cIAP2 sequences as follows: shBcl-x L GAT TGC AAG TTG GAT GGC C; shFLIP-F.1 GGT TCC GAT CAG TTG AAT T; shFLIP-F.2 CAC CTT GTT TCC GAT TAT A; shXIAP-X.1 AGA ATC CTA TGG TGC AAG A; shXIAP-X.2 GGT GCA AGA AGC TAT ACG; shIAP2-I2.1 CAC GGA GAA GGC CAG ATT A and shIAP2-I2.2 GTT CGT TGG CCA AGT TCA A.…”
Section: Plasmidsmentioning
confidence: 99%
“…To determine NF-κB status (RelA/p65 nuclear translocation and NF-κB activity) experiments were performed as described previously [45].…”
Section: Immunofluorescence Of Rela/p65 Nuclear Translocation and Nf-mentioning
confidence: 99%